INTESTINAL HISTOPATHOLOGICAL STUDY, ISOLATION AND MOLECULAR DETECTION OF CLOSTERDIUM PERFERNGES, FROM LAYER CHICKEN IN BASRAH GOVERNORATE - J. Y. Mustafa,; Y. J. Mohammed,; M. A. Abba,; N. J. Khalaf, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was designed for the isolation and molecular identification of Clostridium perfringens. From a total of 200 samples, C. perfringens was isolated from 30 samples (25%) of laying hens and confirmed using a PCR assay by amplifying a segment of a gene (16S rDNA gene) from C. perfringens. The result of histopathology study showed severe necrotic area surrounded by inflammatory cells, erosions of the intestinal epithelium, ulceration of the epithelium, villous necrosis finding surrounded by inflammatory cells, vascular congestion, goblet cell hyperplasia. For the type of toxin, the bacterial isolates were analyzed by PCR using specific primers in order to determine the presence of cpa genes (cpb, iA, cpe, cpb2). Among the 30 C. perfringens isolates, 10 isolates were identified (33.33%) with C. She is type A (carrying the alpha toxin gene). Of these 10 isolates, 5 isolates (50%) were identified as type A simplex and 5 (50%) were identified as heterozygous but no None of the isolates carry both cpb2 and cpe genes. As the dominant species, 20 isolates (66.66%) were identified as C. The research concluded that C. perfringens was one of the most important isolates from laying hens, and the toxin type A was identified as heterozygous (carrying cpb2), and type C is the most prevalent toxin in Basrah, and the detected toxins cause pathological changes in the intestine.